SOCIO-PSYCHOLOGICAL FACTORS OF MOTIVATION FOR SUCCESS AND THE IMPACT OF RISK ON WOMEN - Abdullajonova, Dilnoza (Журнал Педагогики и психологии в современном образовании, 2025)
This article discusses the motivation for success in management, the motivation to avoid defeat, and the level of readiness for risk. Moreover, socio-psychological factors influencing psycho-emotional processes on women’s activity, based on the results of experimental studies, aimed to reveal the motivational characteristics of women by type of leadership